Ocenka psichofiziologiceskogo sostojanija u biatlonistov na etape soveršenstvovanija sportivnogo masterstva - Pavlova, N. V.; Orlova, O. I. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article is devoted to the assessment of the psychophysiological status of biathletes at the stage of improving sportsmanship. Based on the diagnosis of indicators of manual tremor of athletes aged 15-17 years old, the features of arbitrary regulation of movements in a state of relative rest and after performing dosed physical activity are determined.